Exercise capacity after complete repair of tetralogy of Fallot: deleterious effects of residual pulmonary regurgitation. Issue 6 (June 1992) - Carvalho, J S; Shinebourne, E A; Busst, C; Rigby, M L; Redington, A N
Abstract : OBJECTIVE--To determine the effects of residual pulmonary regurgitation on exercise tolerance after complete repair of tetralogy of Fallot. DESIGN--Prospective study of symptom free patients more than five years after complete repair. Graded exercise performance was measured with standard Bruce protocol. Maximal oxygen uptake and ventilatory anaerobic threshold were measured by respiratory mass spectrometry. Measurement of pulmonary regurgitant fraction was from pressure-volume loops constructed from measurements of right ventricular volume obtained from biplane angiograms and simultaneous pressures measured with a micromanometer. SETTING--Tertiary referral centre. PATIENTS--16 patients were studied. Two patients had been excluded because of residual cardiac lesions or inadequate data from cardiac catheterisation. Four were later excluded because they failed to reach a respiratory quotient of greater than 1.0 during graded exercise. RESULTS--There was a significant negative correlation between the degree of residual regurgitation and both total duration of exercise and maximal heart rate achieved. Maximal heart rate and total duration of exercise were significantly lower in the patients than in normal controls. Patients with an abnormal maximal oxygen uptake (less than 85% of the predicted normal value) had significantly greater residual pulmonary regurgitation than those in whom oxygen uptake was normal. CONCLUSIONS--Impaired exercise capacity after complete repair of tetralogy of Fallot is directly related to the degree of residual pulmonary regurgitation. These data should be taken into account when deciding the optimal timing and nature of corrective surgery.